Analysis of Electromechanical Actuator Based on FEM - Circuit Simulator Coupling - Bauer, P.; Sitar, J. (Communications - Scientific letters of the University of Zilina, 2007)
Design and simulation of an electromechanical system is multidisciplinary. In this paper three different types of co-simulation of a mechatronic system are compared. The co-simulation is realized between two different programs (power electronic circuit simulator – control part and finite element analysis – magnetic and mechanic model part). The simulations were realized for an electromechanical actuator fuel injection system. The output waveforms for coil current, forces, inductances and position are compared. Finally the measured waveforms are presented too.